Legal mechanisms for purchasing from a sole supplier by certain types of legal entities: grounds, features of recognition and conclusion of a contract - J. N. Belova (Правоприменение, 2025)
The subject. The author makes an analysis of the legal particularities of purchasing from a sole supplier as compared to other procurement methods applied by certain types of legal entities under the requirements of the Procurement Law, as well as examines the legal issues of concluding a contract with a sole supplier. The object of this study is the relations between the customer and potential sole suppliers within the procurement process and subsequent entry into of the contract, including in case of sole supplier’s evasion to conclude the contract and the customer’s need to force the sole supplier to conclude the contract.The purpose of the study is to examine the civil law relations that develop when a customer chooses a non-competitive method of purchasing from a sole supplier, concludes a contract with it, as well as to identify legal issues such relations in theory and practice. The research methodology is a combination of both general scientific methods (analysis, synthesis, deduction, induction, statistical method) and specific scientific methods (legal comparative and formal legal methods, as well as legal modeling). The statistical method has been actively used in the evaluation of numerical data. The application of specific scientific methods allowed the author to develop recommendations on improvement of legal regulations and optimizing the customer’s procurement procedures.The main results and practical application are as follows. The study introduces a number of characteristics that assess the regulator’s impact on the purchasing relations. The stage of pre-contractual relations with a sole supplier is considered by the author both in the context of entering into contractual relations and recognizing the status of a sole supplier in accordance with the Procurement Law. The lack of a unified approach to procurement of this kind, and a specific set of documents that a potential sole supplier will have before concluding a contract, reduces the legal certainty of the relationships that arise during the procurement process.Conclusions. The author proposes to apply a reasonable approach to select a procurement method, including based on the exceptional nature of procurement from a sole supplier, as well as to avoid uncertainty, to the extent possible, when concluding a contract with a sole supplier.